Enhanced Growth and Activities of the Dominant Functional Microbiota of Chicken Manure Composts in the Presence of Maize Straw - Zhang, Lili; Li, Lijuan; Pan, Xiaoguang; Shi, Zelu; Feng, Xihong; Gong, Bin; Li, Jian; Wang, Lushan (Frontiers in Microbiology, 2018)
As a consequence of intensive feeding, the bulk deposition of livestock manure causes severe environmental problems. Composting is a promising method for waste disposal, and the fermentation process is driven by microbial communities. However, chicken manure contains diverse gut microbes, mainly species derived from Proteobacteria, which may include pathogens that threaten human health. To evaluate composting as a harmless treatment of livestock manure, the dynamics of the microbiota in two chicken manure composts were studied, and the influences of adding maize straw on the compost microbiota were compared. The results revealed that microbes from Firmicutes including Bacillus and Lentibacillus are the most dominant degraders with a strong amino acid metabolism, and they secrete a diverse array of proteases as revealed in metaproteomics data. The addition of maize straw to the chicken manure compost accelerated species succession at the initial stage, and stimulated carbohydrate metabolism in the dominant microbiota. Besides, under the resulting high temperature (> 70C) conditions, the relative abundance of Proteobacteria was reduced by 78% in composts containing maize straw by day 4, which was faster than in compost without added maize straw, in which the abundance was reduced by 66%. Adding maize straw to chicken manure composts can therefore increase the fermentation temperature and inhibit the growth of Proteobacteria. In general, these findings provide increased insight into the dynamic changes among the dominant functional microbiota in chicken manure composts, and may contribute to the optimization of livestock manure composting on an industrial scale.